KONSELING BIBLIOTHERAPY DALAM PERSPEKTIF TINDAKAN SOSIAL SEBAGAI UPAYA PENCEGAHAN PERNIKAHAN DINI DI SMPN 2 MAYANG JEMBER - Lestari, Sri Dwi; Hakim, Moch Lukman (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2024)
This research is based on the background that occurs, namely in Jember every year the number of early marriages continues to increase, so preventive action is needed in the school environment, one of which is by conducting a bibliotherapy counseling approach in the perspective of social action with novel media: Dark Notes of Early Marriage Prahara. So that children can have an understanding of early marriage education. Therefore, this study aims to determine how the implementation of bibliotherapy counseling in the perspective of social action as an effort to prevent early marriage at SMP N 2 Mayang, Jember Regency. Data collection in this study was carried out by observation, interviews and documentation. After the data is collected, the data will be analyzed to get the final result (conclusion). The result of this research is that the counseling process carried out between counseling teachers as counselors and students as counselees, they include performing social actions. As said by Max Wiber, human behavior can be classified into social behavior or not. Behavior can be said to be a social action if the action is related or explored to others. There is a background as well as a purpose to the social action carried out, both as an individual and as an institution. However, each has different social actions, the counseling teacher performs instrumental rational social action where he takes action to write novels with the aim of facilitating students to conduct blibiotherapy counseling in an effort to prevent early marriage. Meanwhile, the four students carry out reading social actions aimed at getting early marriage education, where reading activities are carried out intensely with the counseling teacher which aims to have knowledge related to the impact of early marriage. Of the four informants, after doing blibiotherapy counseling activities, it gave rise to value-oriented social action for 3 students, while 1 student included instrumental rational social action.